Suppression of cyclicity and estrous behavior in mares through immunization against a recombinant gonadotropin-releasing hormone antigen - Spiker, Carlie Rae (Kansas State University, 2009)
Mares in estrus can exhibit erratic and fractious behavior that may adversely affect their ease of handling. Current treatments for suppression of estrus in the mare include an oral progestin, Regu-mate® (Hodgson et al., 2005), uterine insertion of a glass ball (Nie et al., 2003), fetal crushing through rectal palpation (Lefranc, 2004) and surgical sterilization (McCue, 2003). Although effective, all of these procedures are problematic for different reasons. Immunization against an endogenous hormone critical to fertility is an attractive alternative in suppressing estrus; especially if it is less intrusive and reversible. This strategy has been demonstrated by targeting gonadotropin-releasing hormone (GnRH) in gilts (Esbenshade and Britt, 1985), ewes (Clarke et al., 1978), mares (Garza et al., 1986), and heifers (Johnson et al., 1988). The antigen developed for this study was produced using the sequence of the bacterial protein, glutathione-S-transferase (GST) linked to three in-tandem repeats of the mammalian GnRH gene coding sequence (GST-GnRH3). Six reproductively sound mares, between the ages of 3 and 8 years, were used in this study. The anti-GnRH group (n=4) received 1 mg of GST-GnRH3 in 2ml of incomplete Freund’s adjuvant (IFA) as the primary injection. Four weeks later, mares received a single booster injection of 0.5mg of GST-GnRH3 in 1ml of IFA. The control mares (n=2) received similar doses of GST protein only, in identical injection volumes of IFA as the anti-GnRH group. The entire duration of the study ran for 22 weeks from early May through September. Ovaries were monitored three times weekly to track follicular growth and ovulation via transrectal ultrasonography. In addition, all mares were exposed to a stallion twice weekly and observed for estrous behavior. Weekly blood samples were collected to evaluate progesterone levels and serum binding of GnRH. The GST-GnRH3 antigen suppressed follicular activity in all treatment mares within 45 days following the second injection. Estrous behavior was suppressed in all but one mare in the anti-GnRH group. When exposed to the stallion, this mare displayed strong estrous behavior for seven weeks despite her lack of ovarian cyclicity. Follicular activity and estrous behavior remained normal in one of the control mares (avg. cycle length = 20 days). For the final 10 weeks of the study, however, the other control mare developed large follicles but failed to ovulate according to the ultrasound data. This mare did not display estrous behavior during this period, and her progesterone levels remained greater than 2 ng/ml for most of the final 10 weeks of the study. Approximately 2 weeks after the booster injection all anti-GnRH mares had progesterone levels of <1ng/ml. GnRH antibody binding peaked two weeks following booster immunization in all treated mares and remained undetectable in control mares throughout the study. The GST-GnRH3 treatment induced GnRH binding, suppressed follicular activity and reduced progesterone concentrations in all four mares. Although estrous behavior was abolished in 3 of the 4 treated mares, one did continue to demonstrate estrous behavior in the presence of a stallion. This dissociation of ovarian activity and estrous behavior was evident in our study with a limited number of animals, but the vaccine does show promise in reducing unwanted estrous behavior.
Keywords: equine; vaccine; sterilization; GnRH; Agriculture, General (0473)